HADÎTS SEBAGAI LANDASAN PEMBENTUKAN TRADISI ISLAMI - Karimullah Karimullah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2011)
Abstract:   Hadîts both of as basic of Islam law, in the implementation be sure as basic in daily life, that it will appear many dialectics between Hadîts with a local tradition and culture what have been present in the society, even it has been strong roof in the society. Because of that, in this discussion, it will discuss about the function of hadîts in acomodation various of tradition in society, in order to appropriate theory of Islam. The problems what becom main study in this working paper, that is: the first, what are the forms of interaction hadîts in context with tradition in society. Second, context pattern what can connected between both of them. In order to, in acomodation process or Hadîts aculturation into locak tradition in society don’t make trouble what more become wide and dangerous. Until development local culture-tradition what in the society we able to build agree with theory of Islam. Some concept what can be solution, when we want to development Islamic studies especially in Indonesia. That aculturation process between Hadîts and tradition culture what have been development in society become harmonie one of unity, with apply four context system, that is islamization, pribumization, negotiation, and tolerance. And the last will formed a construction process and aculturation of local traditions what is not appropriate with theory of Islam become a tradition Islamic.   Key Words: Hadîts, tradisi, Islamisasi, pribumisasi, negosiasi, dan toleransi